2023
DOI: 10.3390/cancers15072065
|View full text |Cite
|
Sign up to set email alerts
|

Increased SEC23A Expression Correlates with Poor Prognosis and Immune Infiltration in Stomach Adenocarcinoma

Abstract: Background: Previous studies have described that the SEC23A gene is involved in the occurrence and development of various tumor entities. However, little is known about its expression and relevance in stomach adenocarcinoma (STAD). The aim of this study was to bioinformatically analyze the role of SEC23A in STAD, followed by patient tissue sample analyses. Materials and methods: SEC23A expression levels in STAD and normal gastric tissues were analyzed in the Cancer Genome Atlas and Gene Expression Omnibus data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…SEC23A has been reported to be involved in several cancers [ 26 , 55 ]. Recent studies demonstrated that SEC23A was associated with immune infiltration and poor prognosis in GC [ 24 , 56 ]. According to our results, SEC23A was highly expressed in GC tissues and predicted a poor prognosis in GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…SEC23A has been reported to be involved in several cancers [ 26 , 55 ]. Recent studies demonstrated that SEC23A was associated with immune infiltration and poor prognosis in GC [ 24 , 56 ]. According to our results, SEC23A was highly expressed in GC tissues and predicted a poor prognosis in GC patients.…”
Section: Discussionmentioning
confidence: 99%